Wheat cultivars submitted to water deficit at the beginning of flowering in greenhouse - dos Santos, Diego; Guimarães, Vandeir F.; Klein, Jeferson; Fioreze, Samuel L. [UNESP]; Macedo Júnior, Eurides K. (FapUNIFESP (SciELO), 2012)
The water restriction can damage the performance of crops, especially in the flowering period. Thus, the aim of this research was to evaluate the response of genotypes of wheat submitted to water deficit in the beginning of flowering. The experiment was conducted in greenhouse, in a completely randomized design, in factorial scheme 3 x 2, with five replications. The factors studied were: three wheat cultivars (Coodetec (CD) 105, 108 and 111) and 2 irrigation managements (with and without imposition of water deficit). During the period of water deficit imposition, gravimetric soil moisture and the relative content of water in leaf were evaluated, while at the moment of rehydration the biometric variables were determined. At the end of the crop cycle the components of production were evaluated. Reduction was found in the gravimetric soil moisture, in the relative levels of water and in all biometric variables, in function of the water deficit. The grain production showed difference only among the water regimes, in which the cultivar CD 111 is more efficient in the maintenance of the productive potential in conditions of water deficit, through the quick recovery in the relative content of water in leaves.
Cultivares de trigo submetidas a déficit hídrico no início do florescimento, em casa de vegetação
Keywords: Biometric parameters; Irrigation management; Triticum aestivum L.; Water relative content